2014
DOI: 10.1155/2014/168614
|View full text |Cite
|
Sign up to set email alerts
|

Microanatomical Study of Embryonic Gonadal Development in Japanese Quail (Coturnix japonica)

Abstract: Gonadal development of quail embryos was examined histologically using histological and histochemical methods. In the present study, quail embryos were studied at various stages of incubation period based on phases of gonadogenesis. Germ cell migration was observed on day 3-4 but gonadal differentiation and gonadal function were observed on day 6–8 and day 11–14, respectively. During germ cell migration, quail primordial germ cells (qPGCs) were successfully detected in both left and right genital ridges as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…[9,18] The genital ridge located at the medioventral surface of the developing mesonephroi near the base of the dorsal mesentery. [16,18] The current study revealed the boundaries of the undifferentiating gonads were well defined and separated from the mesonephroi. While Chang, Chen found the undifferentiated gonads shared the same parenchyma with the kidney tube suggesting that, [19] some kidney cells shared in the gonadal formation.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…[9,18] The genital ridge located at the medioventral surface of the developing mesonephroi near the base of the dorsal mesentery. [16,18] The current study revealed the boundaries of the undifferentiating gonads were well defined and separated from the mesonephroi. While Chang, Chen found the undifferentiated gonads shared the same parenchyma with the kidney tube suggesting that, [19] some kidney cells shared in the gonadal formation.…”
Section: Discussionmentioning
confidence: 61%
“…[7,15,16] In contrary Fargeix, Didier noted the genital ridge appeared at HH13 (E.2), [17] Sekido and Lovell-Badge marked that it appeared at HH23 (E.4) and Al-Saffar and Ab.Abood claimed the genital ridge appeared at 7-8 days old duck embryo. [9,18] The genital ridge located at the medioventral surface of the developing mesonephroi near the base of the dorsal mesentery.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations